Inventories of Methane Emission for Enteric and Decomposition Gasses from Cattle Manure and Its Mitigation Strategies - Dodi Devitriano; Hutwan Syarifuddin; Jalius Jalius; Yudha Gusti Wibowo (Universitas Diponegoro, 2023)
Livestock is a significant contributor to global methane (CH4) emissions, accounting for 18% to 51% of total emissions worldwide. The purpose of this study is to estimate the CH4 emissions from livestock in Jambi Province, using the Tier-1 method recommended by the Intergovernmental Panel on Climate Change (IPCC). The results show that CH4 emissions range from 7,464,728 to 7,833,349 tons per year, with feces management contributing 160,261 to 166,667 tons per year, and buffalo enteric emissions contributing 2,511,135 to 2,616,185 tons per year. These findings highlight the significant impact of the livestock sector in Jambi Province on global warming. Moreover, this study presents a brief overview of mitigation strategies that can be implemented to reduce CH4 emissions from the livestock sector.